2021
DOI: 10.1038/s41386-021-00971-1
|View full text |Cite
|
Sign up to set email alerts
|

Replicable association between human cytomegalovirus infection and reduced white matter fractional anisotropy in major depressive disorder

Abstract: Major depressive disorder (MDD) is associated with reductions in white matter microstructural integrity as measured by fractional anisotropy (FA), an index derived from diffusion tensor imaging (DTI). The neurotropic herpesvirus, human cytomegalovirus (HCMV), is a major cause of white matter pathology in immunosuppressed populations but its relationship with FA has never been tested in MDD despite the presence of inflammation and weakened antiviral immunity in a subset of depressed patients. We tested the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 135 publications
1
7
0
Order By: Relevance
“…Prior to further processing images, quality checks on diffusion images were performed using QUAD and SQUAD, the automated quality control tool in FSL ( 79 ). Results indicated that all participants fell under the exclusion threshold from previous literature, which was average volume-to-volume head motion of <3 mm or <5% of total outliers ( 80 , 81 ). Visual inspection on the cleaned images confirmed this result, but because diffusion images are especially susceptible to head motion ( 82 ), head motion effects were further tested, as discussed in Control Analyses .…”
Section: Methodsmentioning
confidence: 78%
“…Prior to further processing images, quality checks on diffusion images were performed using QUAD and SQUAD, the automated quality control tool in FSL ( 79 ). Results indicated that all participants fell under the exclusion threshold from previous literature, which was average volume-to-volume head motion of <3 mm or <5% of total outliers ( 80 , 81 ). Visual inspection on the cleaned images confirmed this result, but because diffusion images are especially susceptible to head motion ( 82 ), head motion effects were further tested, as discussed in Control Analyses .…”
Section: Methodsmentioning
confidence: 78%
“…Fronto-occipital connections are implicated in visuospatial processing and motor function ( Makris et al, 2005 ), whilst impaired connectivity of long-distance tracts, such as the fronto-occipital and longitudinal fasciculi, which link several areas involved in pain perception and attention, has been associated with chronic pain ( Geha et al, 2008 ; Rayhan et al, 2013 ). Emerging evidence suggests that systemic inflammation leads to disruption of fronto-occipital WM tract integrity in humans ( Ho et al, 2022 ; Tagliapietra and Monaco, 2020 ; Zheng et al, 2021 ). Neutrophils and CRP did not correlate with edge strength in the current study; however, our PsA sample was small and larger studies are needed to replicate this result.…”
Section: Discussionmentioning
confidence: 99%
“…We recently published some of the rst work linking CMV seropositivity to neuroimaging abnormalities in the context of major depressive disorder (MDD). In up to three independent samples, we demonstrated that compared to CMV seronegative individuals with MDD, CMV positive individuals with MDD had widespread reductions in gray matter volume, decreased white matter integrity in a tract connecting the frontal and occipital lobes (inferior frontal occipital fasciculus), and reduced functional connectivity between hubs of the sensorimotor and salience networks [21][22][23] . Leboyer and colleagues had previously reported that CMV antibody levels were inversely associated with hippocampal volume in individuals with bipolar disorder (BD) and schizophrenia 24 .…”
Section: Introductionmentioning
confidence: 90%